Collaboration in Implementation of Kota Tanpa Kumuh (KOTAKU) Program in Palangka Raya City - Farid Zaky Yopiannor; Novianto Eko Wibowo (Iapa Proceedings Conference, 2019)
The goal number 11 of the 2030 global Sustainable Development Goals (SDG’s) agreement is to make the settlement of an inclusive, safe, resilient and sustainable city. The Public Works and Housing Ministry has held a program to improve the quality of urban services and community-based infrastructure, namely the Kota Tanpa Kumuh (KOTAKU). This program has become one of the priorities of the Palangka Raya City since 2016. The purpose of this study was (1) to analyze the implementation performance of the KOTAKU strategic program in Palangka Raya City; (2) to carry out an analysis of the collaborative process between actors in the KOTAKU program. This research is descriptive qualitative research, where data is obtained through observation, interviews and documentation. The study results show that the performance implementatiton of KOTAKU in Palangka Raya was successful. This can be seen from the total slum area which has been reduced significantly. The dynamics of collaboration show that the interactive cycle between principle engagement, shared motivation and capacity for joint action is going well. The CGR performance is supported by two factors, i.e: political dynamic or power relation and initiating leadership.